Environment Friendly Voltage Up-gradation Model for Distribution Power Systems - K. Nithiyananthan; Umasankar Umasankar (Institute of Advanced Engineering and Science, 2016)
The main aim of this research work is to analyze and develop voltage up gradation procedure model for effective & economic power distribution in urban and suburban area. Voltage up gradation from 6.6KV to 11KV of the distribution power system network has been considered for the proposed research work. Electric power consumption has been increasing uninterruptedly, being this increase specially accelerated in the last few years. Nowadays electric lines are saturated; they are reaching critical values of ampere capacity and sag. Therefore, building new lines has been necessary to provide the ever increasing consumption. The difficulty to find new corridors to construct new distribution lines, underground cables is increasing in cities, industrial areas and in many cases it is simply impossible. The construction of new electric lines is increasing difficulty, thus there is a need to look at alternatives that increases the power transfer capacity. Voltage up gradation of the existing electric cables/lines of the distribution system is the most viable solution and it stresses on the savings of power due to a reduction in system losses when the voltage is high. The proposed research work is to develop and analyze voltage up gradation procedures and protocols for converting 6.6KV network into 11KV network in a distributed system. It also takes into account the expenses incurred in the process and the various other important constraints.